GABLS4, snow model intercomparison. - Le Moigne, P. (Zenodo, 2022)
Content of the archive: FORCING : The near-surface variable forcing dataset used to drive the offline simulations. Time step of 30 minutes, start date 1/12/2009, 15 days. SIMULATIONS : NetCDF output files from participating models. OBSERVATIONS : Surface temperature observation time series and observations of snow temperature in the snowpack at different depths used for the validation. FIGURES : The datasets and the python scripts used to prepare the figures.